Keanekaragam Jenis Udang di Muara Namhoi Kecamatan Mempawah Hilir Kabupaten Mempawah, Kalimantan Barat - Maulani, Tari; Padmarsari, Widadi (Akuatik Tropis: Journal of Tropical Aquatic Resource Management, 2024)
ABSTRACTShrimp are members of the Crustacea subphylum which can be found in fresh waters to marine waters. Shrimp diversity is very important to know, especially in the Namhoi Estuary which is an active fishing area for both fish and shrimp. The aim of the research is to determine the diversity of shrimp in Muara Namhoi which includes relative abundance, diversity index, uniformity index, dominance index and environmental parameters. The research was carried out for ± 2 months, namely July"“September 2023 in Muara Namhoi, Mempawah Hilir subdistrict, Mempawah recency, West Kalimantan. The method used is purposive sampling with sampling carried out 2 times at each station. The fishing gear used is a 1 inch trammel net. The results of the research were 4 families with 11 types and a total of 663 individual shrimp. The highest relative abundance is in the Penaeidae family with the genera Metapenaeus and Parapenaeopsos and the Dogol Shrimp/Metapenaeus affinis type (Milne Edwards, 1837). The diversity index for shrimp species in Muara Namhoi ranges between 1.43-1.87, which is considered medium, uniformity between 0.60-0.78 is considered uniform and dominance between o.20-0.32 is considered low. Environmental factors in the Muara Namhoi are included in the good category for shrimp life with temperatures between 27.5ËšC-30ËšC, current speed 0.03 m/s, brightness between 28 cm-42.4 cm, pH 7.6, depth between 146.5 cm-225 cm, Salinity 28.5 ppt, DO between 7.3 mg/l "“ 7.7 mg/l. It is suspected that if shrimp are caught in their juvenile period, it is necessary to regulate the size of shrimp suitable for catching and provide provisions for areas for catching shrimp so that shrimp fry can breed in the Muara Namhoi.  Keywords: Shrimp Diversity, Shrimp Types, Muara Namhoi